ANALISIS RISIKO GREEN SUPPLY CHAIN MANAGEMENT AGROINDUSTRI BIOETANOL (STUDI KASUS DI PT. ENERGI AGRO NUSANTARA) - Bambang Herry Purnomo; Luluk Sinta Devi; Winda Amilia (AGROINTEK, 2021)
PT. Energi Agro Nusantara is a company engaged in the field of renewable energy, namely producing bioethanol made from molasses. In carrying out its business activities, PT. Energi Agro Nusantara applies the concept of Green Supply Chain Management (GSCM), but in the implementation of green manufacturing there are still complex problems including raw materials being scattered, production machine breakdowns, byproducts that have not been utilized optimally. These problems have the potential to cause risks that can harm the company. This study aims to determine the risk events and sources of risk that can occur and design a management strategy that can be used to reduce the incidence of risk sources. on GSCM agroindustry bioethanol activities. The method used in this research is the House of Risk (HOR) which consists of 2 phases, namely HOR phase 1 is used to identify risks that occur in supply chain activities and HOR phase 2 is used to arrange preventive measures from priority risks. The results showed that there were 24 risk events and 33 identified sources of risk. From HOR phase 1, 9 priority risk sources were obtained which were taken into consideration in the preparation of handling strategies. From HOR phase 2, obtained 5 priority handling strategies.